Green synthesis of silver nanoparticles and their inhibitory effects on resistant udder pathogens - Silvia Ondrašovičová; František Zigo; Zuzana Farkašová; Zuzana Lacková; Oksana Velgosova; Lívia Mačák; Jana Záhumenská; Ewa Pecka-Kiełb; Mária Vargová; Jana Ondrašovičová; Ibrahim F. Rehan (Journal of Applied Animal Research)
The study covers a new process for synthesizing silver nanoparticles using dry lavender leaves (Lav-AgNPs) as a reducing and stabilizing agent, and evaluation of their inhibitory effect on the resistant udder pathogens. Of all 480 investigated dairy cows, 402 cows (83.8%) had a negative CMT score, and 78 cows (16.2%) had a positive CMT score (5.6% quarters), of which 94 (4.9%) represented quarters infected with a bacterial pathogen. The most frequent udder pathogens were non-aureus staphylococci (NAS), isolated from 46.7% of all positive samples. Other important udder pathogens were Staphylococcus aureus (S. aureus) (19.1%) and Streptococcus uberis (Str. uberis) (10.7%). Generally, the isolated staphylococci and Str. uberis showed high resistance to β-lactams and aminoglycosides. In particular, isolates that showed resistance to penicillin and gentamycin were tested for the inhibitory effect of pure AgNPs and synthesized Lav-AgNPs. Lav-AgNPs at a concentration of 200 ppm showed strong resistance to the tested pathogens, and an inhibition zone of 13±0.73 mm was formed for S. aureus, 16±1.15 mm for Staphylococcus chromogenes (S. chromogenes), 14±0.52 mm for Staphylococcus haemolyticus (S. haemolyticus), and 14±0.56 mm for Str. uberis. In conclusion, green synthesis provides an anti-bacterial product that represents an alternative to antibiotic substances.